Workshop Penyusunan Perangkat Pembelajaran Berbasis TIK di Kecamatan Cidaun Kabupaten Cianjur - Anik Yuliani; Heris Hendriana; Aflich Yusnita Fitriana; Sheilla Zalzabilla Aljabar; Ansori Ansori (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Education serves as an essential foundation that cannot be replaced in efforts to build a sustainable society. In this era of globalization, educational challenges are becoming increasingly complex, requiring continuous innovation and adaptation to ensure optimal learning quality for all segments of society. Cianjur Regency, as an integral part of Indonesia's development, located in West Java Province, faces unique challenges in improving the quality of education. One of the districts requiring special attention is Cidaun District. Despite its significant potential, challenges in education persist, particularly in understanding and utilizing various teaching methods, insufficient use of technology, and low student engagement, which hinder the development of the education system in this area. In response to these challenges, a community engagement approach serves as a strong foundation, focusing on empowering the local community to enhance and innovate learning. This community engagement activity takes place over two days in the form of a workshop introducing innovative teaching strategies in the classroom and utilizing technology in learning